Going, Going, Gone? The Apparent Demise of the Accruals Anomaly - Green, Jeremiah; Hand, John R. M.; Soliman, Mark T. (Management Science, 2011)
Consistent with public statements made by sophisticated practitioners, we document that the hedge returns to Sloan's (Sloan, R. G. 1996. Do stock prices fully reflect information in accruals and cash flows about future earnings? Accounting Rev. 71(3) 289–315) accruals anomaly appear to have decayed in U.S. stock markets to the point that they are, on average, no longer reliably positive. We explore some potential reasons why this has happened. Our empirical analyses suggest that the anomaly's demise stems in part from an increase in the amount of capital invested by hedge funds into exploiting it, as measured by hedge fund assets under management and trading volume in extreme accrual firms. A decline in the size of the accrual mispricing signal, as measured by the magnitude of extreme decile accruals and the relative persistence of cash flows and accruals, may also play a (weaker) role. This paper was accepted by Stefan Reichelstein, accounting.